Impact of kidney transplantation on functional status - Hatem Ali; Karim Soliman; Mahmoud M. Mohamed; Manzur Rahman; Johann Herberth; Tibor Fülöp; Ingi Elsayed (Annals of Medicine)
Background and aims Functional capacity (FC) is known to affect morbidity and mortality in kidney transplantation. Despite this important role, little is known about the variables influencing post-transplant FC. Our study aims at identifying these crucial associations.Method Our study included 16,684 renal transplant recipients (RTR). Patients had transplant between 1 September 2018 and 1 September 2019. Mild functional impairment was defined as those with a KPSS score > or = 80; moderate functional impairment was defined as those with a KPSS score between 50 and 70 and severe functional impairment was defined as those with a KPSS score < or =40. The outcome measured was FC at follow-up one-year post-transplant. Abnormal FC at follow-up was defined as those with KPSS score less than 80%. Normal FC at follow-up was defined as those with KPSS score equal or above 80%. Multivariate logistic regression was used to assess with the relationship between patient characteristics and abnormal functional status post-transplant.Results Three groups were identified; those with none-to-mild functional impairment at time of transplant (Group A; n = 8388), those who had moderate impairment at time of transplant (Group B; n = 7694) and those who had severe impairment at time of transplant (Group C; n = 602). Abnormal FC at one-year post transplant was present in 7.69%, 28.89%, 49.49% of patients in group A, B and C, respectively. Glucocorticoid withdrawal was associated with lower risk of developing abnormal FC post-transplant (OR = 0.75, p value = .02, 95% confidence intervals: 0.64 to 0.97), while recipient diabetes was associated with higher risk of abnormal FC (OR = 1.44, p value <.01, 95% confidence intervals: 1.20 to 1.74) in adjusted model.Conclusion Kidney transplantation is associated with substantial improvement in all stages of FC in KTRs. Glucocorticoid withdrawal and diabetes mellitus are potentially modifiable factors of FC and merit further considerations during pre-transplant workup and post-transplant immunosuppressive therapeutic planning.Key messagesKidney transplantation is associated with substantial improvement in all stages of FC in KTRs.Glucocorticoid withdrawal and diabetes mellitus are potentially modifiable factors of FC and merit further considerations during pre-transplant workup and post-transplant immunosuppressive therapeutic planning.